2016
DOI: 10.1111/acel.12528
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants reveal an inverted U‐shaped dose‐response relationship between reactive oxygen species levels and the rate of aging in Caenorhabditis elegans

Abstract: SummaryReactive oxygen species (ROS) are potentially toxic, but they are also signaling molecules that modulate aging. Recent observations that ROS can promote longevity have to be reconciled with the numerous claims about the benefits of antioxidants on lifespan. Here, three antioxidants [N‐acetylcysteine (NAC), vitamin C, and resveratrol (RSV)] were tested on Caenorhabditis elegans mutants that alter drug uptake, mitochondrial function, and ROS metabolism. We observed that like pro‐oxidants, antioxidants can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…mTOR inhibition extends life span and improves age‐related pathologies in a variety of species . Interestingly, a recent report established that mTOR is activated through a PI3K/Akt/mTOR pathway during replicative senescence in vascular smooth muscle cells . Linking geroconversion to oxidants, we have shown that activation of Akt by a O 2 •− ‐driven prooxidant state mimics growth‐factor signaling and promotes proliferation in the absence of growth factors .…”
Section: Oxidants and Cellular Senescence Beyond Cell Cycle Arrestmentioning
confidence: 70%
See 1 more Smart Citation
“…mTOR inhibition extends life span and improves age‐related pathologies in a variety of species . Interestingly, a recent report established that mTOR is activated through a PI3K/Akt/mTOR pathway during replicative senescence in vascular smooth muscle cells . Linking geroconversion to oxidants, we have shown that activation of Akt by a O 2 •− ‐driven prooxidant state mimics growth‐factor signaling and promotes proliferation in the absence of growth factors .…”
Section: Oxidants and Cellular Senescence Beyond Cell Cycle Arrestmentioning
confidence: 70%
“…In an effort to understand the molecular pathways involved in geroconversion, it was shown that PI3K/Akt/mTOR pathway is upregulated in aging cells compared to young cells. Inhibitors of PI3K or mTOR blocks the cellular changes in old cells toward senescence . Moreover, Akt deficiency makes cells more resistant to replicative senescence, while activation of Akt shortens the lifespan of human endothelial cells .…”
Section: Oxidants and Cellular Senescence Beyond Cell Cycle Arrestmentioning
confidence: 99%
“…Indeed, PQQ-induced lifespan extension was abolished upon treatment with the antioxidant NAC (Benrahmoune et al, 2000;Desjardins et al, 2017) (Fig. 4A; Fig.…”
Section: Bli-3-dependent Ros Production Is Necessary and Sufficient Fmentioning
confidence: 96%
“…Given that low levels of ROS, namely mtROS and DUOX-mediated ROS, extend lifespan, the intake of vitamins could eliminate such low levels of ROS and cancel their longevity-promoting effects (Desjardins et al, 2017). We propose that PQQ is an effective chemical in lifespan extension acting through generating longevity-promoting ROS at the plasma membrane by the peroxidase and dual oxidase system, which is a fundamentally different action from those of existing antioxidants.…”
Section: Pqq Is a Lifespan Extension Chemical With A Novel Action Mecmentioning
confidence: 97%
“…Although ectopic overexpression of the peroxiredoxin Prx5 increases lifespan in Drosophila (Radyuk et al ., 2009), indicating that decreasing ROS production can attenuate the mitochondrial death spiral as expected, the effects of feeding antioxidants on lifespan have been inconsistent. Difficulties in enabling antioxidant access to the cytoplasm might represent one issue, as the effectiveness of specific antioxidants can vary depending on the precise method of antioxidant presentation (Shibamura et al ., 2009; in data interpretation include the difficulty in determining the Desjardins et al ., 2017). Additional difficulties extent to which the antioxidant feeding actually reduces the cytoplasm.…”
Section: Role Of Antioxidants In Lifespanmentioning
confidence: 99%